Electrolyte Disturbances in Acute Exacerbation of COPD - Rashid, Md Haroon ur (Journal of Enam Medical College, 2019)
Background: Chronic obstructive pulmonary disease (COPD) is a major cause of chronic morbidity and mortality worldwide. Acute exacerbation is an acute and sustained worsening of a patient’s condition from a stable state and it is associated with significant electrolyte disturbances. Objectives: The main objective of this study was to determine the prevalence of electrolyte disturbances in patients with acute exacerbation of COPD and to determine possible effects of these electrolyte disorders. Materials and Methods: This observational prospective study was carried out in the Department of Pulmonology, Enam Medical College & Hospital from 1st January to 31st December 2017. Sixty patients with acute exacerbation of COPD were included. Serum electrolytes and arterial blood gases were measured. Results: Low level of serum sodium (131 ± 5.66 mEq/L) and potassium (3.20 ± 0.44 mEq/L) were found in subjects with acute exacerbation of COPD. In patients with respiratory failure Na+ and K+ levels were even lower. Conclusion: Serum electrolytes in acute exacerbation of COPD patients should be monitored routinely and should be corrected early to avoid poor outcomes. J Enam Med Col 2019; 9(1): 25-29